Compromise: What Makes it Bad? - Biggar, Nigel (Studies in Christian ethics, 2018)
This article considers what makes a compromise bad. First, it defines a compromise as a decision involving a loss of good (i.e., an evil), which should therefore be accompanied by agent-regret. Regret, however, is not moral guilt. Pace proponents of dirty hands, a morally right compromise cannot retain elements of moral wrongness (as distinct from non-moral evil). Second, the article proceeds to elaborate the features of bad compromise further in terms of common moral sense: the preference of less rather than more of a single good; the preference of an inferior to a superior good; and the violation of an absolute moral rule. Third, it extends its elaboration in terms of three historical cases: the abandonment of strategic promotion of a good; tactical suspension for insufficient reasons; complicity in indubitable and certain injustice to avoid tolerable costs; and the violation of a basic principle of justice as distinct from normal judicial process. Finally, it adds a methodological epilogue, in which it reflects on whether its treatment of the topic has been sufficiently theological.